Rule: (Cut Dispute as Possible Duty) And its Jurisprudential and Legal Applications: Family Conciliation and Reform in Jordanian Shari’a Courts as a Model - Qudah , Zakaria Mohammed Faleh (Dirasat: Shari'a and Law Sciences, 2020)
The study investigated the meaning of the fiqhi rules, its emergence and importance and the differences between it and fiqhi restrictions. The study explained that the rule of (dissolution of the dispute when possible) as mentioned by those words in the text in Al-sharkasi Al-hanfi. In the fiqhi and original sources for the four sects with differences in some words; they clarified rule، evidences and vocabularies. The study showed that the dissolution of the dispute is a duty، and this is achieved by preventing its causes and resolving its material from the outset. Islamic Shari prevented disputes and conflicts between people. All that leads to the dispute is forbidden for its evils. If, however, the conflict has occurred as a result of the inevitable human encounter . It must be addressed and ended by all legitimate means possible. The study mentioned a number of jurisprudential applications of this rule in the sources of jurisprudence of the four schools of thought and a number of legal applications within the framework of judicial application in the Family Reform and Reconciliation Department in the Shari'a Courts in the Hashemite Kingdom of Jordan. The study had many results, the most important of which is that the tolerant Islamic Sharia came to prevent disputes and disputes between people.